Understanding the Impact of Artificial Intelligence on Workforce Structures and Social Organizations - Olludotun, Babattunde; Kayode, Oluwaseun; Tunde, Segun (Journal Social Humanity Perspective, 2023)
The study uses qualitative methods to investigate ways in which artificial intelligence (AI) is changing organization structures, workplace organization and the experiences of individuals. Although productivity and automation are broadly described in existing studies, this work examines the social and emotional sides of using AI. The authors came to these results by talking to professionals from different sectors and uncovering new patterns of role ambiguity, more use of algorithm-based decisions and the quiet protests against AI. What findings show is that AI creates new problems of stress and uncertainty when it changes both task division and classic role distinctions. The way organizational hierarchies work is now determined largely by those involved in creating and understanding AI systems. Artificial intelligence also tends to decrease spontaneous social interactions and help people depend on automatic data services. Because of these changes, workers may feel both supervised and excluded from workplace culture. The research adds to the existing readings on AI and employment by looking closely at the social and ethical impacts of using AI. The report advises making AI governance more about supporting people through transparency, letting people take part and paying attention to their emotional needs. Offering insights based on real-world evidence, this work helps policy makers, organizational leaders and experts studying social effects of technological change.